The underlying cognitive mechanisms of the rater effect in creativity assessment: The mediating role of perceived semantic distance. (September 2019) - Guo, Jiajun; Ge, Ying; Pang, Weiguo
Highlights: Highly original people, compared to their less original counterparts, tend to give generally lower ratings to others' ideas. This tendency is more salient when highly original people use explicit criteria which emphasize the unusual aspect of creativity. The tendency is more significant when highly original people use the implicit theory of creativity to evaluate strange ideas. Highly original people's tendency to underestimate others' original ideas is more apparent when the products being evaluated are the combinations of remote ideas/concepts. Perceived semantic distance mediates the effect of rater's originality on ratings of originality. Abstract: It is accepted fact that people often disagree with each other when they evaluate the creativity or originality of a product. At least three types of factors have been found to influence judgements of creativity, including people's own originality, product characteristics, and evaluation criteria. However, little research has systematically investigated those influences, especially their interactions. In addition, the underlying cognitive mechanisms of the influences are still unknown. The purpose of the present study, therefore, was to first examine how evaluations of creativity depend on rater's originality, on the variations in two underlying dimensions of creativity in products – originality and usefulness, and on variations in criteria. A further aim was to investigate the cognitive underpinning of those influences on the basis of both the associated theory of creativity and spreading-activation theory. Two experiments were conducted. In Experiment one, 156 students in a Chinese university completed an Alternative Uses test (AUT) and two creativity ratings tasks using different criteria. The results of Experiment 1 demonstrate that highly original people, compared to their less original counterparts, tend to give lower ratings to others' ideas 1) when they use explicit criteria, which emphasize the unusual aspect of creativity, to evaluate creative as well as strange ideas, and 2) when they use the implicitly theory of creativity to evaluate strange ideas. In Experiment two, another 151 students completed an AUT task, a distance rating task, and an originality rating task. The results indicate that highly original raters' tendency of underestimation is more apparent when the products being evaluated are the combinations of remote ideas/concepts, which suggests that perceived semantic distance mediates the effect of rater's originality on ratings of originality.